Reliability of three pain assessment tools in children requiring dental treatment: A comparative clinical study - Priya Nagarwal; Vivek Rana; Nikhil Srivastava; Noopur Kaushik; Tushar Pruthi (Wolters Kluwer Medknow Publications, 2023)
Background: The appropriate intervention of pain is based on its accurate evaluation, which is a challenge in the pediatric population as they often do not have the language development or cognitive sophistication to describe it correctly. Untreated pain has a negative impact on the psychosocial well-being of children. Aim and Objectives: The study aimed to evaluate and compare the reliability of different pain assessment scales, namely, the Wong Baker Facial Pain Rating scale (WBFPS), Modified Emoji Pain Scale (MEPS), and indigenously developed indigenously made GIF Pain Scale (SPGPS) in children undergoing dental treatment under local anesthesia (LA). Materials and Methods: The study included 152 children aged 4-6 years with a Frankl behavior rating of score 3 and 4 (positive and definitely positive) requiring dental treatment under LA. After local infiltration, each child with two independent observers was asked to record the response of the current pain on the WBFPS, MEPS, and SPGPS. The reliability of the pain scales was assessed on the basis of similar responses given by all three individuals. Results: The Pearson correlation test was performed to determine the correlation among the scales. A very strong correlation was found between the WBFPS and SPGPS (r = 0.848), while a moderate correlation was found among the WBFPS and MEPS (r = 0.691). A strong correlation was found between the SPGPS and MEPS (r = 0.723). Conclusion: The SPGPS proved to be a more reliable pain assessment tool compared to the WBFPS and MEPS in clinical pediatric dentistry.